Comparative study of microstructural and humidity-sensing properties of graphene-based nanocomposite thin film. (20th December 2019) - Rahim, Ishrat; Shah, Mutabar; khan, Afzal; Wahab, Fazal; Iqbal, Mahmood
Abstract: This article reports enhancement of the humidity-sensing properties of graphene (Gr) by the formation of nanocomposites with silver nanoparticles (AgNPs) and poly-methyl methacrylate (PMMA). Ultraviolet/visible spectroscopic study of the prepared materials confirms the formation of Gr and its nanocomposites. The relative capacitance/resistance, sensitivity and response/recovery time of the surface type Cu/Gr/Cu, Cu/Gr + AgNPs/Cu and Cu/Gr + AgNPs + PMMA/Cu humidity sensors are investigated under controlled relative humidity (RH) levels at 300 K. Comb-type interdigitated copper electrodes with a gap of 50 µm are thermally evaporated on a clean plastic substrate and a thin film of Gr and its nanocomposites is deposited on the surface of the pre-deposited interdigitated metallic electrodes using the drop-casting method. Analysis by x-ray diffraction and scanning electron microscopy shows the crystallinity and morphology of the as-deposited thin film surface. Raman spectroscopy is used to analyse the chemical structure, polymorphism and number of layers of the deposited thin films. The humidity-sensing investigation (30%–95% RH) shows an increasing capacitive and resistive response of the fabricated sensors due to the hydrophobic nature of the material at various input frequencies. The response and recovery times for capacitive and resistive Gr-based sensors are much shorter than the earlier reported values in the literature. The present investigation could be useful for fabrication of sensors for commercial applications.